Towards a definition of lost places - Bauer, Christian; Dolgan, Christoph (ERDKUNDE, 2020)
Places juxtaposing normative and heterodox orders have long been a terrain for geographic research. This paper focuses on derelict architectonical structures understood as disordered places outside the norm. Despite the variety of research directions, there is still a lack of a uniform terminology and definition of these places. Following the academic literature, but also the public perception, we term those places as ‘lost places’. Based on an intensive literature research and a four-year empirical fieldwork, we present main trajectories and driving agents on the origin of lost places. We identify the key elements of the origin of lost places in the loss of functionality of architectonical structures and their re-contextualization through different appropriation processes. Both elements portray these architectonical structures as multitemporal and multimodal palimpsests. Finally, we propose a transition concept that offers the epistemological basis for studying lost places.